Dickens's Working Notes for 'Dombey and Son': - Laing, Tony (Open Book Publishers, 2017)
"This critical edition of the working notes for Dombey and Son (1848) is ideal for readers who wish to know more about Dickensâ s craft and creativity. Drawing on the authorâ s manuscript in the Victoria and Albert Museum, Londonâ and containing hyperlinked facsimilesâ Dickensâ s Working Notes for Dombey and Son offers a new digital transcription with a fresh commentary by Tony Laing. Unique and innovative, this is the only edition to make Dickensâ s working methods visible. John Mullan has called Dombey and Son Dickensâ s ""first great novel.â Set amid the coming of the railways, it tells the story of a powerful manâ typical of the commercial and banking magnates of the periodâ and the effect he has on his family and those around him. Laing presents the worksheets and other materials (transcribed for the first time) that together grew into the novel. Reading the book alongside this edition of the notes will enlarge the understanding of Dickensâ s art among teachers, students, researchers and Dickens enthusiasts. As cultural tastes shift from print to digital, Dickensâ s Working Notes will help preserve Dickensâ s work for the future. The magnifying and linking functions of the edition mean that the notes are more easily and usefullyâ not to mention accessiblyâ exhibited here than elsewhere. Laing gives present-day readers the chance not only to recapture the effect of serial publication but also to gain greater insight into the making of a work which by general agreement, and Dickensâ s own admission, has a special place in his development as a novelist."